Mabel Meed, a North-West Mounted Police officer and others on shore during a trip on the steamboat PROSPECTOR, Stewart River, Yukon Territory, 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.198 [Meed journal: "Str "Prospector" on one of the Stewart River trips. My wife stands on shore with N.W.M.P. officer at right."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number